Blasius and Sakiadis problems in nanofluids - Ahmad, Syakila; Mohd Rohni, Azizah; Pop, Ioan (Springer Wien, 2011)
The classical problems of forced convection boundary layer flow and heat transfer past a semi-infinite static flat plate (Blasius problem) and past a moving semi-infinite flat plate (Sakiadis problem) using nanofluids are theoretically studied. The similarity equations are solved numerically for three types of metallic or nonmetallic nanoparticles such as copper (Cu), alumina (Al2O3), and titania (TiO2) in the base fluid of water with the Prandtl number Pr = 6.2 to investigate the effect of the solid volume fraction parameter φ of the nanofluids. Also, the case of conventional or regular fluid (φ = 0) with Pr = 0.7 is considered for comparison with known results from the open literature. The comparison shows excellent agreement. The skin friction coefficient, Nusselt number, and the velocity and temperature profiles are presented and discussed in detail. It is found that the solid volume fraction affects the fluid flow and heat transfer characteristics.